Implementation of Technology Acceptance Model (TAM): Case Study on Generation Z in North Purwokerto Who Uses the BSI Mobile Application - Muarrifah, Safrina; Nur Azizah Rahma Wijaya (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
The rapid advancement in technology and information is particularly prominent in the banking sector. This technology is essential in everyday life, especially among Generation Z, who are highly digitally literate and frequent users of digital banking services. Bank Syariah Indonesia has capitalized on this digital opportunity by providing a mobile banking service called BSI Mobile. Comprehending the factors that affect the utilization of mobile banking is vital for the banking sector. To elucidate the adoption of this technology, this research applies the Technology Acceptance Model (TAM). The aim of this study is to assess the extent to which perceived usefulness, perceived ease of use, and attitudes toward technology influence the adoption of BSI mobile banking among Generation Z in North Purwokerto. This research employed purposive sampling to gather a sample, with primary data gathered through online questionnaires distributed via Google Forms to 124 respondents. The research is quantitative, utilizing multiple linear regression analysis with the assistance of SPSS version 25.0 software. The findings indicate that perceived usefulness does not have a significant impact on the use of BSI mobile banking among Generation Z in North Purwokerto. However, the variable for perceived ease of use and attitude toward technology usage positively affects BSI mobile banking usage in this group. Furthermore, the independent variables collectively have a positive and significant impact on the dependent variable, demonstrated by the F-test result where Fcount > Ftable (36.946 > 2.68) and a significant value (0.00 < 0.05). The R² is 48.0%, indicating that 48.0% of the variation in mobile banking usage is elucidated by the three independent variables: 1) perceived usefulness (X1), 2) perceived ease of use (X2), and 3) attitude toward technology usage (X3).